OSTOMİLİ HASTALARIN ÖZ BAKIM GÜCÜ VE OSTOMİYE UYUMLARININ DEĞERLENDİRİLMESİ - KARATEPE, MEDET (Fırat Üniveristesi, 2022)
Ostomi açılma girişimleri hastanın yaşam sürecini değiştiren, alıştığı ve sürdürdüğünden farklı bir yaşam biçimine geçişe neden olan zor bir süreçtir. Hastaların öz bakım gücü ostomiye uyumlarını olumlu yönde etkilemektedir. Bu araştırma ostomili hastaların öz bakım gücü ve ostomiye uyumlarını değerlendirmek amacıyla yapılmıştır. Tanımlayıcı tipte olan bu araştırma Şubat 2020- Haziran 2022 tarihleri arasında yürütülmüştür. Araştırmanın evrenini Elazığ Fethi Sekin Şehir Hastanesi ve Fırat Üniversitesi Hastanesi Genel Cerrahi servislerindeki ostomili hastalar oluşturmuştur. Araştırma örneklemini, bu evrenden olasılıksız rastlantısal örnekleme yöntemiyle seçilen 106 ostomili hasta oluşturmuştur. Verilerin toplanmasında Kişisel Bilgi Formu, Özbakım gücü Ölçeği (ÖGÖ) ve Ostomi Uyum Ölçeği (OUÖ) kullanılmıştır. Verilerin değerlendirilmesinde tanımlayıcı istatistikler, Anova, t testi ve korelasyon analizi testleri kullanılmıştır. Hastaların yaş ortalaması 54,58±15,81'dir. Araştırmamıza katılan hastaların özbakım gücü düzeyi 84,26±23,93 puan ortalamasıyla orta düzeyde bulunmuştur. Araştırmamızda hastaların uyum düzeyi 38,43±6,58 puan ortalamasıyla orta düzeyde olduğu bulunmuştur. Araştırmaya katılan hastaların ÖGÖ ve OUÖ puanları arasındaki ilişki incelendiğinde aralarında pozitif yönde önemli ilişkinin olduğu bulunmuştur (p<0,05). Hastaların öz bakım gücü düzeyi arttıkça ostomiye uyumlarının arttığı saptanmıştır. Hastaların öz bakım gücü ve uyumlarını arttırmak için ameliyat öncesi dönemde başlayarak ostomi bakımı eğitimi verilmesi önerilebilir. Anahtar Kelimeler: Hemşirelik, Ostomi, Öz bakım, Uyum

Ostomy opening attempts are a difficult process that changes the life process of the patient and causes the transition to a different life style from the patient is used to and maintains. The strength of self-care of patients positively affects their adaptation to an ostomy. This study was conducted to evaluate the self-care agency of patients with an ostomy and their compliance with an ostomy. This descriptive study was conducted between February 2020 and June 2022. The patients with an ostomy in the General Surgery Departments of Elazığ Fethi Sekin City Hospital and Fırat University Hospital constituted the target population of the research. The sample population of the research consisted of 106 patients with ostomies selected from this population by an improbable accidental sampling method. Personal Information Form, Self-Care Agency Scale (SCAS), and Ostomy Adjustment Inventory (OAI) were used to collect the data. Descriptive statistics, ANOVA, t-test, and correlation analysis tests were used to evaluate the data. The mean age of the patients was 54.58±15.81 years. The level of self-care agency of the patients participating in our study was found to be moderate with an average of 84.26±23.93 points. In our study, it was found that the adjustment level of the patients was moderate with an average of 38.43±6.58 points. When the relationship between the SCAS and OAI scores of the patients recruited in the study was examined, it was found that there was a significant positive relationship between them (p<0.05). It was determined that as the level of self-care agency of the patients increased, their adaptation to ostomy increased. To increase the self-care agency and adjustment of patients, it may be recommended to provide ostomy care training starting from the preoperative period. Keywords: Nursing, Ostomy, Self-Care, Adjustment
Evaluation of the self-care agency of patients with ostomy and their compliance with Ostomy
Keywords: Hemşirelik